The biodiversity of urban and peri-urban forests and the diverse ecosystem services they provide as socio-ecological systems (2016)
Urban and peri-urban forests provide a variety of ecosystem service benefits for urban society. Recognising and understanding the many human-tree interactions that urban forests provide may be more complex but probably just as important to our urbanised society. This paper introduces four themes that link the studies from across the globe presented in this Special Issue: (1) human-tree interactions; (2) urban tree inequity; (3) carbon sequestration in our own neighbourhoods; and (4) biodiversity of urban forests themselves and the fauna they support. Urban forests can help tackle many of the "wicked problems" that confront our towns and cities and the people that live in them. For urban forests to be accepted as an effective element of any urban adaptation strategy, we need to improve the communication of these ecosystem services and disservices and provide evidence of the benefits provided to urban society and individuals, as well as the biodiversity with which we share our town and cities. © 2016 by the authors.